(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
This paper presents a proposal of deployment of the Catarinense Attendance Service/CAS to the, aiming to innovate information management in the Legislative Assembly. The object of study is the processing of information in the attendance sector. This investigation follows the guiding principles of innovation, knowledge and change management applied to a public organization.